2020
DOI: 10.1021/acsaem.0c00243
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Control on the Energy Storage Performance of PANI@PVA@ACNT-Based Flexible Solid-State Supercapacitors

Abstract: In this work, a redox and an electrochemical polymerization method were carried out separately to produce the composite PANI@PVA@ACNT-based flexible solid-state supercapacitor (FSC) device with symmetrical "sandwich structure". Interestingly different polymerization methods result in different spatial structures, which lead to significant difference in the ion transport behaviors and energy storage mechanisms. The redox-polymerized aniline (R-PANI) provides a 3D polyaniline network in the gel system which exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
(75 reference statements)
0
18
0
Order By: Relevance
“…Flexible supercapacitors (FSCs) are new emerging energy storage devices having great mechanical compliance and high power density, making them suitable as power back-ups for next-generation flexible electronics because they could work under bending and even twisting states. , Depending upon the storage mechanism, supercapacitors (SCs) can be categorized as pseudocapacitors , and electrochemical double-layer capacitors (EDLCs) . Carbon-based materials such as carbon fibers, carbon nanotubes, activated carbon, and graphene (GN) , are consider as best electrode materials for EDLCs,whereas conjugated polymers (CPs) and transition metal oxides (TMOs) and phosphides have been used as electrodes in Faradaic-capacitors/pseudocapacitors because of their reversible redox processes and high surface area. It is recognized that conducting polymers are optimal electrode materials for stretchable energy storage devices …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible supercapacitors (FSCs) are new emerging energy storage devices having great mechanical compliance and high power density, making them suitable as power back-ups for next-generation flexible electronics because they could work under bending and even twisting states. , Depending upon the storage mechanism, supercapacitors (SCs) can be categorized as pseudocapacitors , and electrochemical double-layer capacitors (EDLCs) . Carbon-based materials such as carbon fibers, carbon nanotubes, activated carbon, and graphene (GN) , are consider as best electrode materials for EDLCs,whereas conjugated polymers (CPs) and transition metal oxides (TMOs) and phosphides have been used as electrodes in Faradaic-capacitors/pseudocapacitors because of their reversible redox processes and high surface area. It is recognized that conducting polymers are optimal electrode materials for stretchable energy storage devices …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Depending upon the storage mechanism, supercapacitors (SCs) can be categorized as pseudocapacitors 13,14 and electrochemical double-layer capacitors (EDLCs). 15 Carbon-based materials such as carbon fibers, 16 carbon nanotubes, 17 activated carbon, 18 and graphene (GN) 19,20 are consider as best electrode materials for EDLCs,whereas conjugated polymers (CPs) 21 and transition metal oxides (TMOs) 22 and phosphides 23 have been used as electrodes in Faradaiccapacitors/pseudocapacitors because of their reversible redox processes and high surface area. It is recognized that conducting polymers are optimal electrode materials for stretchable energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…ASCs especially usually combine advantages of the two different types of electrodes, which can provide a high capacitance and a long cycle life [ 4 ]. As a main component of SCs, various electro-active materials have been explored, such as carbonaceous materials (carbon nanotubes [ 5 , 6 , 7 ] (CNTs), graphene [ 8 , 9 ] and active carbon [ 10 ]), transition metal-based materials (RuO 2 [ 11 ], MnO 2 [ 12 ], NiO [ 13 ], Co 3 O 4 [ 14 ]), sulfides [ 15 ], metal selenides [ 16 ] and conducting polymers (PANI [ 17 ], PPy [ 18 ], PEDOT [ 19 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al synthesized a PANI/PVA/CNTbased flexible supercapacitor with a specific capacitance of 896 mF/cm 3 along with good cyclic stability and excellent rate performance. 43 Mn-ion-doped Ni−Co-layered double hydroxide nanosheet-coated polyaniline-derived carbon was fabricated by Cao et al This showed a higher specific capacitance of 1282.06 C/g and 82.66% capacity retention following 10 000 cycles, exhibiting a high energy density of 78.9 Wh/kg at a power density of 1.55 kW/kg. 44 Hsu et al 45 developed a nanocellulose-based polyaniline-reduced graphene oxide sandwich-like supercapacitor electrode with high flexibility, mechanical strength, and conductivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nowadays, great endeavors have gone into the most felicitous choice of materials for developing a hybrid supercapacitor. Ye et al synthesized a PANI/PVA/CNT-based flexible supercapacitor with a specific capacitance of 896 mF/cm 3 along with good cyclic stability and excellent rate performance . Mn-ion-doped Ni–Co-layered double hydroxide nanosheet-coated polyaniline-derived carbon was fabricated by Cao et al This showed a higher specific capacitance of 1282.06 C/g and 82.66% capacity retention following 10 000 cycles, exhibiting a high energy density of 78.9 Wh/kg at a power density of 1.55 kW/kg .…”
Section: Introductionmentioning
confidence: 99%